2017
DOI: 10.1111/are.13333
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation ofHaematococcus pluvialispowder on gonadal development, coloration and antioxidant capacity of adult male Chinese mitten crab (Eriocheir sinensis)

Abstract: The green algae Haematococcus pluvialis is an important source of natural astaxanthin as feed additive. This study was conducted to investigate the effects of dietary supplementation of H. pluvialis powder on gonadal development, coloration and antioxidant capacity of adult male Chinese mitten crab Eriocheir sinensis, and four experimental diets were formulated to contain 0, 0.2%, 0.4% and 0.6% of H. pluvialis powder. There were four treatments (defined as D1~D4) in this study and each treatment had three repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 39 publications
5
14
0
Order By: Relevance
“…T‐AOC levels showed a trend of “U shape pattern” with increasing dietary H. pluvialis supplementation and the highest level was observed in T3 diet, which indicated that suitable dietary H. pluvialis could enhance the antioxidant capacity of L. maculates . This result was in accordance with previously published researches on discus fish Symphysodon haraldi (Wang et al., 2016) and Chinese mitten crab Eriocheir sinensis (Wu et al., 2017). H. pluvialis can accumulate high‐content astaxanthin which has significant effects on scavenging free radicals and improving antioxidant capacity of aquatic animals (Chien & Shiau, 2005; Sheikhzadeh, et al., 2012a, 2012b).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…T‐AOC levels showed a trend of “U shape pattern” with increasing dietary H. pluvialis supplementation and the highest level was observed in T3 diet, which indicated that suitable dietary H. pluvialis could enhance the antioxidant capacity of L. maculates . This result was in accordance with previously published researches on discus fish Symphysodon haraldi (Wang et al., 2016) and Chinese mitten crab Eriocheir sinensis (Wu et al., 2017). H. pluvialis can accumulate high‐content astaxanthin which has significant effects on scavenging free radicals and improving antioxidant capacity of aquatic animals (Chien & Shiau, 2005; Sheikhzadeh, et al., 2012a, 2012b).…”
Section: Discussionsupporting
confidence: 93%
“…CAT, SOD and GPX are closely relevant to scavenge free radicals and protect the important cellular macromolecules and organelles from oxidative damage (Firat et al., 2011; Misra & Niyogi, 2009; Wang et al., 2018). Our results showed that the levels of CAT, SOD and GPX in the liver of L. maculates decreased significantly with increasing dietary H. pluvialis , similar to the results on Chinese mitten crab Eriocheir sinensis (Wu et al., 2017), large yellow croaker Pseudosciaena crocea (Li et al., 2014) and juvenile olive flounder Paralichthys olivaceus (Pham et al., 2014). The higher the antioxidant enzymes level is, the more superoxide radicals need to be eliminated (Yang et al., 2010).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Based on this method, in this study, we used the L16 (4 5 ) orthogonal array, which arranged five factors varied at four levels (Table 2) to test the effect of combined VE, NT, H.P, ARA and YE on the growth and reproduction of female RC crayfish according to Ref. (Arshadi et al., 2018; Li et al., 2018; Wu et al., 2017; Xu, Zhang, et al, 2017; Zhang et al., 2019), respectively. The detailed ingredients of the diets used in these sixteen trials for RC crayfish are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%